Maternally derived immunity in young mice to infection with Trypanosoma brucei and its potentiation by Berenil chemotherapy - Whitelaw, D.D.; Urquhart, G.M. (Wiley, 1985)
Summary Young mice which were allowed to suckle, from birth, a mother infected with Trypanosoma brucei, or a mother whose infection had been cured before parturition with Berenil chemotherapy, were themselves immune to homologous trypanosome challenge. This immunity extended until approximately 25 days of age, and was transmitted in the colostrum/milk of the mother. Mice born of infected mothers, but transferred at birth to normal foster mothers, were susceptible to trypanosome infection. Drug prophylaxis in normal newborn mice was also effective for approximately 25 days, but in mice which, in addition, received colostral antibody from the mother, combined immunochemoprophylaxis protected the offspring for 40–50 days. Since the combination of protective strategies continued to resist challenge beyond the stage when, on its own, each component's efficacy had decayed, it may be of practical value as an approach to improved disease control under certain field conditions where trypanosomiasis prevails.